Forest Offences In Protected Areas: An Appraisal To Maqasid Shariah In Federal And State Government Relationship - Adzidah Yaakob; Intan Nadia Ghulam Khan (Usim Press, 2024)
Volume: 34 No:3 (page : 1-13)